Markers of coagulation and inflammation and adverse events in patients with active cancer and atherosclerosis: common features and differences - Yu. A. Fedotkina; A. L. Komarov; А. В. Dobrovolsky; E. N. Krivosheeva; О. О. Frolkova; E. V. Titaeva; T. V. Balakhonova; Е. Р. Panchenko (Атеротромбоз)
Introduction. Thrombotic complications (TC) in different vascular systems dictate the fate of high-risk patients. In cardiological practice, patients with advanced atherosclerotic vascular disease (MFA) represent the most vulnerable group. Malignant neoplasm (MN) is one of the most significant risk factors for developing TCs, especially in the context of antineoplastic therapy. The presence of significant differences in the mechanisms of thrombogenesis in malignant neoplasms and atherosclerosis determines the appropriateness of a comparative study of markers of coagulation activation and endothelial damage in order to identify common features and differences specific to each pathology. Aim. To examine markers of coagulation activation and growth factors in active cancer and advanced atherosclerotic vascular disease, to identify their common features and differences specific to each pathology.  Materials and methods. A total of 22 patients with MN (Group 1) and 58 patients with MFA (Group 2) were enrolled in the study. The assessed biomarkers included: von Willebrand factor (VWF), D-dimer, growth differentiation factor-15 (GDF-15) and vascular endothelial growth factor A (VEGF-A).  Results. Patients with MN had an increased likelihood of disease progression within 6 months at D-dimer level > 1121 ng/mL (OR = 10.5; 95% CI 1.4–81.0, p = 0.014) or VWF > 189% (OR 10.5, 95% CI 1.36–81.0, p = 0.014); the likelihood of death within two years of follow-up at D-dimer level > 1121 ng/mL (OR = 7.0; 95% CI 0.97–50.57, p = 0.04), or VWF > 203% (OR = 10, 5, 95% CI 1.36–81.06, p = 0.014). In patients with MFA, the likelihood of prognosis determining events within one-year of follow-up was determined by increased levels of VWF > 157% (OR = 9.2, 95% CI 1.02–82.8, p = 0.048) and GDF-15 > 1548 pg/ml (OR = 5.7; 95% CI 1.09–29.5, p = 0.04).  Conclusions. Endothelial damage and coagulation activation are more pronounced in patients with MN than in patients with MFA. In patients with malignant neoplasms, the outcomes were associated with D-dimer and VWF levels, and in patients with MFA – with VWF and GDF-15 levels.